La justice est indivisible : la Palestine comme enjeu féministe - Elia, Nada (Revue PréfiX, 2024)
L’article traduit ici en français s’inscrit précisément dans cette démarche d’interpellation critique des féministes non-palestiniennes, y compris juives et racisées. Le titre « Justice is indivisible » reprend une déclaration de Martin Luther King Jr., et le sous-titre, « Palestine as a feminist issue », est inspiré d’un texte d’Angela Davis. Le texte est paru en 2017 dans un numéro spécial intitulé « Palestine Lives » de la revue aujourd’hui en dormance, Declonization : Indigenity, Education & Society, qui proposait aussi des articles comparant l’apartheid sud-africain et israélien (Leigh-Ann Naidoo) ou le colonialisme de peuplement aux États-Unis et en Israël (Johanna Fernandez). La traduction de ce texte est une initiative du Chantier sur l’antiféminisme du Réseau québécois en études féministes (RéQEF). En termes politiques, il y a alors une dizaine d’années que la bande de Gaza, minuscule territoire où s’entasse une population pauvre, y compris dans des camps de réfugié·es, est sous le contrôle du Hamas. Cette force politique islamiste en a expulsé de manière plutôt brutale le parti laïque du Fatha, du président palestinien Mahmoud Abbas qui contrôle encore aujourd’hui la Cisjordanie, menacée par les attaques de colons. En Occident, le Hamas est souvent diabolisé par la majorité comme l’équivalent palestinien de l’État islamique en Irak et en Syrie ou des talibans afghans, une force autoritaire, voire totalitaire, réactionnaire et patriarcale. Rappelons pour mémoire que bien des féministes aux États-Unis ont appuyé l’invasion militaire de l’Afghanistan par la coalition menée par les États-Unis, en 2001, tant elles espéraient voir les talibans vaincus, pour libérer les Afghanes. Pour leur part, bien des Afghanes rappelaient que leur problème principal restait la désolation que leur apportaient la guerre et la violence de l’occupation militaire occidentale, des propos qui font échos à ceux de Nada Elia au sujet de la Palestine écrasée par l’armée israélienne. Ce texte est aussi une réaction à la période 2015-2016, marquée par un regain de tensions meurtrières entre Israël et la Palestine, y compris quelques attaques aux couteaux menées par des Palestiniens à Jérusalem, qui ont attirées l’attention sur la scène internationale. En termes de rapports de force et de capacités de lutte, ces attaques aux couteaux doivent pourtant être comparées à la puissance de feu de l’armée israélienne, et même de colons, qui provoque évidemment bien plus de morts et blessés du côté palestinien qu’Israélien. L’armée israélienne, par exemple, compte 10 fois plus de chars d’assaut que l’armée française et 20 fois plus que l’armée canadienne. Le Hamas n’a pas de chars d’assaut… La publication de cette version française a été en grande partie motivée par la turbulence provoquée par l’offensive des troupes du Hamas lancée le 7 octobre qui a provoqué plus de 1 000 victimes du côté israélien, et surtout la réplique israélienne qui, à ce jour, a provoqué plus de 30 000 victimes du côté de Gaza, ainsi qu’un déplacement de plus de la moitié de la population et la destruction d’une ampleur inégalée, y compris d’hôpitaux, d’universités, d’écoles et de bibliothèques (sans parler des morts qui s’accumulent aussi en Cisjordanie). Cette violence à grande échelle a provoqué des ondes de choc dans les réseaux universitaires, y compris féministes, en Amérique du Nord et en Europe, alors que des voix (pro)palestiniennes ont été muselées par les directions d’établissement (voir, à ce sujet, Francis Dupuis-Déri, « Où sont les défenseurs de la liberté universitaire ? », Le Devoir, 25 janvier 2024). Même si le texte de Nada Elia est plutôt pessimisme à ce sujet, et traduit un terrible isolement politique, notons que quelques féministes juives se mobilisent aujourd’hui contre le génocide, dont la célèbre Judith Butler, qui réclame publiquement un cessez-le-feu, le droit de retour pour la population palestinienne et le démantèlement des structures coloniales, ainsi que Rosalind Pollack Petchesky, 81 ans, qui avait étudié l’antiféminisme et la nouvelle droit dans les années 1980, qui a codirigé en 2021 avec Esther Farmer et Sarah Sills l’ouvrage A Land With A People : Palestinians and Jews Confront Zionism et qui a été récemment arrêtée à deux reprises à New York dans des mobilisations du groupe Jewish Voice for Peace contre le gouvernement israélien et l’appui qui lui offre le gouvernement des États-Unis. Pendant ce temps, le Palestinian Feminist Collective appelle pour le 8 mars à participer à la campagne Third World Women Resist, à Chicago, Détroit, Los Angeles et San Francisco, déclarant qu’on « constate que des “féministes” sionistes, colonialistes et impérialistes s’approprient le vocabulaire des droits des femmes pour discréditer la lutte de libération palestinienne » et qu’« il n’y a pas de place pour des génocidaires et leurs alliées dans des mouvements féministes anti-impérialistes et décoloniaux. »
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme décolonial; génocide; impérialisme; intersectionnalité; palestine; préFiX; régions géographiques; système colonial; systèmes d'oppressions; thématiques; traduction; violences

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis